THE EFFECTS OF READING HABIT AND VOCABULARY MASTERY TOWARDS DESCRIPTIVE WRITING SKILL (Survey at Private Junior High Schools in Bekasi) - Tri Wulansari Adlina; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2022)
The purpose on this research is to know whether there are significant effects of reading habit and vocabulary mastery towards descriptive writing skill. The research was conducted at SMP Tahta Syajar, SMP At-taqwa 06 and SMP Seroja Bekasi of the eighth grade with the total population of 534 students and the sample was 75 students that were randomly taken. The method used in the research was a survey. Data of reading habit, vocabulary mastery and descriptive writing skill were collected from a test. The data analysis used correlation and multiple regression which showed the data requirements test (normality test and linearity test), before the regression test was carried out.Data collection done by giving essay test for descriptive writing skill, thirty (30) items of multiplechoice test for Reading Habit, and twenty (30) items of multiplechoice test for vocabulary mastery given to the subjects at SMP Tahta Syajar, SMP At-taqwa 06 and SMP Seroja Bekasi. The result of data analyzes shows that: 1) There is significant effect of reading habit and vocabulary mastery jointly towards descriptive writing skill. This is evidenced by the acquisition of the value Sig = 0.000 <0.05 and Fcount = 62.376. 2) There is significant effect of reading habit towards descriptive writing skill. This is evidenced by the acquisition of the value Sig = 0.000 < 0.05 and tcount = 9.298. 3) There is significant effect of reading habit towards descriptive writing skill. This is evidenced by the acquisition of the value Sig = 0.001 < 0.05 and tcount = 3.330.